A Longitudinal Analysis of Well‐Being of Ghanaian Children in Transnational Families. Issue 5 (19th June 2017) - Cebotari, Victor; Mazzucato, Valentina; Appiah, Ernest
Abstract : This study is the first to employ panel data to examine well‐being outcomes—self‐rated health, happiness, life satisfaction, and school enjoyment—of children in transnational families in an African context. It analyzes data collected in 2013, 2014, and 2015 from secondary schoolchildren and youth (ages 12–21) in Ghana ( N  =   741). Results indicate that children with fathers, mothers, or both parents away and those cared for by a parent, a family, or a nonfamily member are equally or more likely to have higher levels of well‐being as children in nonmigrant families. Yet, there are certain risk factors—being a female, living in a family affected by divorce or by a change in caregiver while parents migrate—that may decrease child well‐being.